Sequence variants in the PTCH1 gene associate with spine bone mineral density and osteoporotic fractures - Styrkarsdottir, Unnur; Thorleifsson, Gudmar; Gudjonsson, Sigurjon A.; Sigurdsson, Asgeir; Center, Jacqueline R.; Lee, Seung Hun; Nguyen, Tuan V.; Kwok, Timothy C.Y.; Lee, Jenny S.W.; Ho, Suzanne C.; Woo, Jean; Leung, Ping-C.; et al. (Nature communications, 2016)
Bone mineral density (BMD) is a measure of osteoporosis and is useful in evaluating the risk of fracture. In a genome-wide association study of BMD among 20,100 Icelanders, with follow-up in 10,091 subjects of European and East-Asian descent, we found a new BMD locus that harbours the PTCH1 gene, represented by rs28377268 (freq. 11.4–22.6%) that associates with reduced spine BMD ( P =1.0 × 10 −11 , β =−0.09). We also identified a new spine BMD signal in RSPO3 , rs577721086 (freq. 6.8%), that associates with increased spine BMD ( P =6.6 × 10 −10 , β =0.14). Importantly, both variants associate with osteoporotic fractures and affect expression of the PTCH1 and RSPO3 genes that is in line with their influence on BMD and known biological function of these genes. Additional new BMD signals were also found at the AXIN1 and SOST loci and a new lead SNP at the EN1 locus. Bone mineral density (BMD) is the best predictor of osteoporotic fracture risk. Here, the authors perform a genome wide association study in Icelanders and people of European and East-Asian descent, and identify a new allele in intron 15 of the PTCH1 gene that associates with reduced BMD.